Decompressive Hemicraniectomy and Favorable Outcome in a Pediatric Patient with Malignant Middle Cerebral Artery Infarction - Ricardo Barrientos; Carlos Sisniega; Samanta Catueno; Robin Hougen; Ashley Hanna; Utpal Bhalala (Hindawi Limited, 2022)
We report a rare case of middle cerebral artery (MCA) stroke in a teenage girl with initial improvement, followed by progression to malignant MCA infarction, requiring an urgent decompressive hemicraniectomy (DHC). Additionally, we report improvement in all areas, including language, comprehension, and motor skills at discharge and the 4-month follow-up. This rare presentation highlights the importance of monitoring the neurological status of a patient with an MCA infarct for progression to a life-threatening malignant MCA infarct. This case report also highlights the importance of consideration of DHC for a favorable outcome of the MMCA infarction.